Evolutionarily Conserved and Non-Conserved Roles of Heterotrimeric Gα Proteins of Plants. (7th April 2022) - Pandey, Sona; Roy Choudhury, Swarup; Ha, Chien Van; Mohanasundaram, Boominathan; Li, Mao; Dodds, Audrey
Abstract: Heterotrimeric G-proteins modulate multiple signaling pathways in many eukaryotes. In plants, G-proteins have been characterized primarily from a few model angiosperms and a moss. Even within this small group, they seem to affect plant phenotypes differently: G-proteins are essential for survival in monocots, needed for adaptation but are nonessential in eudicots, and are required for life cycle completion and transition from the gametophytic to sporophytic phase in the moss Physcomitrium (Physcomitrella) patens . The classic G-protein heterotrimer consists of three subunits: one Gα, one Gβ and one Gγ. The Gα protein is a catalytically active GTPase and, in its active conformation, interacts with downstream effectors to transduce signals. Gα proteins across the plant evolutionary lineage show a high degree of sequence conservation. To explore the extent to which this sequence conservation translates to their function, we complemented the well-characterized Arabidopsis Gα protein mutant, gpa1, with Gα proteins from different plant lineages and with the yeast Gpa1 and evaluated the transgenic plants for different phenotypes controlled by AtGPA1. Our results show that the Gα protein from a eudicot or a monocot, represented by Arabidopsis and Brachypodium, respectively, can fully complement all gpa1 phenotypes. However, the basal plant Gα failed to complement the developmental phenotypes exhibited by gpa1 mutants, although the phenotypes that are exhibited in response to various exogenous signals were partially or fully complemented by all Gα proteins. Our results offer a unique perspective on the evolutionarily conserved functions of G-proteins in plants.